2018
DOI: 10.1002/jbm.a.36356
|View full text |Cite
|
Sign up to set email alerts
|

Surface sulfonamide modification of poly(N‐isopropylacrylamide)‐based block copolymer micelles to alter pH and temperature responsive properties for controlled intracellular uptake

Abstract: Two different surface sulfonamide-functionalized poly(N-isopropylacrylamide)-based polymeric micelles were designed as pH-/temperature-responsive vehicles. Both sulfadimethoxine- and sulfamethazine-surface functionalized micelles were characterized to determine physicochemical properties, hydrodynamic diameters, zeta potentials, temperature-dependent size changes, and lower critical solution temperatures (LCST) in both pH 7.4 and 6.8 solutions (simulating both physiological and mild low pH conditions), and tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Unlike side chain modification, the α-end modification of P­(NIPAAm/AIPAAm-PMM) with hydrophilic Alexa Fluor 488 moderately affected the polymer LCST. This result is in good agreement with the previous research, in which modifying PNIPAAm with various hydrophobic phenyl derivatives on its end resulted in less than 10 °C of LCST shift, whereas hydrophilic modification of the end group only increased the LCST by up to 5 °C. ,, These results therefore point out the superior effect of side chain modification to fine-tune the LCST relative to copolymerization PNIPAAm with ionizable monomers and end modification.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Unlike side chain modification, the α-end modification of P­(NIPAAm/AIPAAm-PMM) with hydrophilic Alexa Fluor 488 moderately affected the polymer LCST. This result is in good agreement with the previous research, in which modifying PNIPAAm with various hydrophobic phenyl derivatives on its end resulted in less than 10 °C of LCST shift, whereas hydrophilic modification of the end group only increased the LCST by up to 5 °C. ,, These results therefore point out the superior effect of side chain modification to fine-tune the LCST relative to copolymerization PNIPAAm with ionizable monomers and end modification.…”
Section: Discussionsupporting
confidence: 92%
“…Effect of Hydrophilicity of Polymer Terminus. Since previous studies have reported that hydrophilicity of the terminus critically affects LCST, 3,31 we next examined the effect of the end group of P(NIPAAm/AIPAAm-PMM) on the LCST. The α-terminus was conjugated with hydrophilic Alexa Fluor 488 dye (Figure 4a), and LCST behavior was evaluated by light scattering analysis.…”
Section: ■ Resultsmentioning
confidence: 99%
“…For example, pH/temperature‐responsive nanocarriers were prepared from two sulfonamide‐functionalized poly( N ‐isopropylacrylamide)‐based polymeric micelles ( Figure 11 ). [ 210 ] When loaded with a proof‐of‐concept antiproliferative drug, both sulfadimethoxine surface‐functionalized and sulfamethazine surface‐functionalized micelles demonstrated enhanced intracellular uptake under mildly acidic conditions (pH 6.8) at temperatures slightly above their lower critical solution temperatures. Both micelle variations possessed the capability to be used as an intracellular pH/temperature responsive drug or gene delivery system.…”
Section: Stimulus‐responsive Nanocarrier Delivery Systemsmentioning
confidence: 99%
“…b) pH-dependent property changes of the sulfonamide derivative. a,b) Reproduced with permission [210]. Copyright 2018, Wiley-VCH.…”
mentioning
confidence: 99%
“…Smart polymers that respond to the external stimuli such as pH, redox potential, and enzymes have attracted intense interest in biological applications. In particular, various pH-responsive polymers have been employed to construct stimulus-responsive nanoplatforms for tumor therapy and imaging. Among them, polymers with sulfadimethoxine (SDM) groups show a very sharp transition range and remarkably pH-dependent solubility resulting from the ionization of the functional groups in the acid tumor microenvironment (TME), providing a reasonable tactic to design stimulus-responsive CAs. In addition, a special attention has been paid to the host–guest adamantane/β-CD (Ad/β-CD) complexation in the design of nanostructured materials, due to the strong association constant on account of the great fitness of Ad into β-CD cavity. In the present work, we designed and prepared polysulfadimethoxine (PSDM)-modified ESIONPs based on the Ad/β-CD complexation as a pH-responsive T 1 /T 2 switchable contrast agent to selectively activate the T 2 MRI signal at the tumor region. Polyethylene glycol (PEG) terminally modified with adamantane (Ad-PEG-NH 2 ) was introduced on the surface of ESIONPs to obtain adamantane-modified ESIONPs (ESIONPs-PEG-Ad).…”
Section: Introductionmentioning
confidence: 99%